ANALISIS PERBEDAAN CHLORALHIDRAT DAN ESTAZOLAM TERHADAP ONSET TIDUR DAN EKSESSIF GELOMBANG BETA PADA PASIEN ANAK YANG DILAKUKAN PEMERIKSAAN EEG - Taufik Hidayat, Malisa Ariani, Ali Rahman Hakim (AKPER Pemkab Purworejo, 2022)
ABSTRACT Background: The cause of the seizure can be analyzed and known the cause and the course of the disease. One of the technological advances in the field of health to see or vertical the diagnosis of seizures is the examination of EEG or Electro Encephalo Graft. In conducting EEG examinations on children, premedication is needed that aims for the success and success of the EEG examination process and the results of EEG recordings. Purpose: Knowing the analysis of the difference between the administration of chloral hydrate and estazolam to sleep onset and beta wave excessef in pediatric patients conducted an EEG examination at Poliklinik Neuroelecttromedic Ulin Banjarmasin Hospital. Method: This research method is quantitative observational analytics with Cross Sectional design and uses convenience sampling techniques. Results: Onset sleeps for the premedication of chloralhydrate mean (26.33). In the premedication estazolam mean (26.13). The analysis found that in the premedication of EEG using chloralhydrate drugs there was no excess of beta waves of 13 people (86.7%). In the premedication of estazolam obtained the number of excesses of beta wave 5 people (33.3%). The results of the sleep onset analysis test using the mann whitney test obtained a mean premedication rank of chloralhydrate 15.60, statistical test results obtained a value of p = 0.947. Results of beta wave excess analysis test using chi square test obtained value p value = 0.390 Conclusion: There was no difference in premedication of chloralhydrate and estazolam to sleep onset and beta wave excessef in pediatric patients who performed EEG examinations. Keywords: chloralhydrate and estazolam, EEG, onset of sleep and excessef of beta waves